Using the NIH Toolbox to Assess Cognition in Adolescents and Young Adults with Autism Spectrum Disorders. Issue 3 (2nd October 2020) - Solomon, Marjorie; Gordon, Andrew; Iosif, Ana‐Maria; Geddert, Raphael; Krug, Marie K.; Mundy, Peter; Hessl, David
Abstract : Despite the clinically significant impact of executive dysfunction on the outcomes of adolescents and young adults with autism spectrum disorders (ASD), we lack a clear understanding of its prevalence, profile, and development. To address this gap, we administered the NIH Toolbox Cognition Battery to a cross‐sectional Intelligence Quotient (IQ) case‐matched cohort with ASD ( n = 66) and typical development (TD; n = 66) ages 12–22. We used a general linear model framework to examine group differences in task performance and their associations with age. Latent profile analysis (LPA) was used to identify subgroups of individuals with similar cognitive profiles. Compared to IQ case‐matched controls, ASD demonstrated poorer performance on inhibitory control ( P < 0.001), cognitive flexibility ( P < 0.001), episodic memory ( P < 0.02), and processing speed ( P < 0.001) (components of Fluid Cognition), but not on vocabulary or word reading (components of Crystallized Cognition). There was a significant positive association between age and Crystallized and Fluid Cognition in both groups. For Fluid (but not Crystallized) Cognition, ASD performed more poorly than TD at all ages. A four‐group LPA model based on subtest scores best fit the data. Eighty percent of ASD belonged to two groups that exhibited relatively stronger Crystallized versus Fluid Cognition. Attention deficits were not associated with Toolbox subtest scores, but were lowest in the group with the lowest proportion of autistic participants. Adaptive functioning was poorer in the groups with the greatest proportion of autistic participants. Autistic persons are especially impaired on Fluid Cognition, and this more flexible form of thinking remains poorer in the ASD group through adolescence. Lay Summary: A set of brief tests of cognitive functioning called the NIH Toolbox Cognition Battery was administered to adolescents and young adults with autism spectrum disorders (ASD; n = 66) and typical development (TD; n = 66) ages 12–22 years. Compared to TD, ASD showed poorer performance in inhibiting responses, acting flexibly, memorizing events, and processing information quickly (Fluid Cognition). Groups did not differ on vocabulary or word reading (Crystallized Cognition). Crystallized and Fluid Cognition increased with age in both groups, but the ASD group showed lower Fluid, but not Crystallized, Cognition than TD at all ages. A categorization analysis including all participants showed that most participants with ASD fell into one of two categories: a group characterized by poor performance across all tasks, or a group characterized by relatively stronger Crystallized compared to Fluid Cognition. Adaptive functioning was poorer for participants in these groups, which consisted of mostly individuals with ASD, while ADHD symptoms were lowest in the group with the greatest proportion of TD participants.